Winter warmings, tides and planetary waves. Comparisions between CMAM (with interactive chemistry) and MFR-MetO observations and data. - Hall, Chris; Manson, A.H.; Meek, C.; Chshyolkova, T.; McLandress, C.; Avery, S.K.; Fritts, D.C.; Hocking, W.K.; Igarashi, K.; MacDougall, J.W.; Murayama, Y.; Riggin, D.C.; et al. (European Geosciences Union, 2006)
Following earlier comparisons using the Canadian Middle Atmosphere Model (CMAM, without interactive chemistry), the dynamical characteristics of the model are assessed with interactive chemistry activated. Time-sequences of temperatures and winds at Tromsø (70° N) show that the model has more frequent and earlier stratospheric winter warmings than typically observed. Wavelets at mesospheric heights (76, 85 km) and from equator to polar regions show that CMAM tides are generally larger, but planetary waves (PW) smaller, than medium frequency (MF) radar-derived values. Tides modelled for eight geographic locations during the four seasons are not strikingly different from the earlier CMAM experiment; although monthly data now allow these detailed seasonal variations (local combinations of migrating and non-migrating components) within the mesosphere (circa 50–80 km) to be demonstrated for the first time. The dominant semi-diurnal tide of middle latitudes is, as in the earlier papers, quite well realized in CMAM. Regarding the diurnal tide, it is shown here and in an earlier study by one of the authors, that the main characteristics of the diurnal tide at low latitudes (where the S (1,1) mode dominates) are well captured by the model. However, in this experiment there are some other unobserved features for the diurnal tide, which are quite similar to those noted in the earlier CMAM experiment: low latitude amplitudes are larger than observed at 82 km, and middle latitudes feature an unobserved low altitude (73 km) summer maximum. Phases, especially at low and middle (circa 42° N) latitudes, do not match observations well. Mesospheric seasonal tidal variations available from the CUJO (Canada U.S.\ Japan Opportunity) radar (MFR) network (sites 40–45° N) reveal interesting longitudinal differences between the CMAM and the MFR observations. In addition, model and observations differ in the character of the vertical phase variations at each network-location. Finally, the seasonal variations of planetary wave (PW) ...